Cost-effectiveness of 13-valent pneumococcal conjugate vaccine (PCV13) in older Australians. Issue 34 (3rd August 2017) - Dirmesropian, S.; Wood, J.G.; MacIntyre, C.R.; Beutels, P.; McIntyre, P.; Menzies, R.; Reyes, J.F.; Chen, C.; Newall, A.T.
Abstract: Background: The 23-valent pneumococcal polysaccharide vaccine (PPV23) has been funded under the Australia National Immunisation Program (NIP) since January 2005 for those aged >65 years and other risk groups. In 2016, PCV13 was accepted by the Pharmaceutical Benefits Advisory Committee (PBAC) as a replacement for a single dose of PPV23 in older Australian adults. Methods: A single-cohort deterministic multi-compartment (Markov) model was developed describing the transition of the population between different invasive and non-invasive pneumococcal disease related health states. We applied a healthcare system perspective with costs (Australian dollars, A) and health effects (measured in quality adjusted life-years, QALYs) attached to model states and discounted at 5% annually. We explored replacement of PPV23 with PCV13 at 65 years as well as other age based vaccination strategies. Parameter uncertainty was explored using deterministic and probabilistic sensitivity analysis. Results: In a single cohort, we estimated PCV13 vaccination at the age of 65 years to cost ∼A11, 120, 000 and prevent 39 hospitalisations and 6 deaths from invasive pneumococcal disease and 180 hospitalisations and 10 deaths from community acquired pneumonia. The PCV13 program had an incremental cost-effectiveness ratio of ∼A88, 100 per QALY gained when compared to a no-vaccination, whereas PPV23 was ∼A297, 200 per QALY gained. To fall under a cost-effectiveness threshold of A60, 000 per QALY, PCV13 would have to be priced below ∼A46 per dose. The cost-effectiveness of PCV13 in comparison to PPV23 was ∼A35, 300 per QALY gained. Conclusion: In comparison to no-vaccination, we found PCV13 use in those aged 65 years was unlikely to be cost-effective unless the vaccine price was below A46 or a longer duration of protection can be established. However, we found that in comparison to the PPV23, vaccination with PCV13 was cost-effective. This partly reflects the poor value for money estimated for PPV23 use in Australia.